Pengaruh Pembiasaan Latihan Sholat Dzuhur Berjama’ah Terhadap Sikap Kedisiplinan di Rumah - Apriani, Luthfiyah; Ramadhani, Chali Via (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
The purpose of this study was to find out how the habit of practicing congregational dzuhur prayer and whether it had affects the attitude of discipline at home of grade 1 students. the population in this study was all students of class 1 SD Bunayya Pagar Alam, amounting to 61, and the sample in this study was grade 1 students, totaling using total sampling techniques and quantitative descriptive methods. The collection techniques for this research were in the form of observation, questionnaires, and documentation. The data analysis used validity, reliability, normality, linearity, and hypothesis with simple linier regression. The results of the descriptive analysis on the habit of practicing congregational dzuhur prayer were in the “ adequate” category, which was shown in the average score of 25,67. The results of the simple linier regression the showed that there was no effect of the habit of practicing congregational prayer with a disciplined attitude at home as seen based on a significance value of 0,176 > 0,05 and an R Square value 0.064 which means that only 6,4% variation in discipline attitudes at home is explained by the habit of congregational dzuhur prayers at school.